The Effect of Business Capital on Business Development in MSMEs in Bandung Regency Moderated by MSME Training - Tia Yulia Aisyah; Asep Mulyana; Cupian Cupian (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to 1) test and analyze the influence of business capital on business development in culinary MSMEs in Bandung Regency, 2) test and analyze the influence of business capital on business development in moderation of MSME training in culinary MSMEs in Bandung Regency, the approach used is quantitative with the type of research used in this study is a survey. The technique used in sampling is non-probability sampling with purposive sampling. This study involved 156 food MSMEs in Bandung Regency that have been active for approximately the past three years, are MSMEs that are members of the Packaging Clinic program fostered by the Bandung Regency Industry and Trade Office. The analytical tool used is PLS-SEM, the results of this study indicate that 1) there is a significant positive influence of business capital on business development, 2) there is a significant positive influence of business capital on business development moderated by MSME training. This study suggests that culinary MSMEs in Bandung Regency can utilize MSME training which is one of the local government programs to obtain business capital so that there is effective business development.